2018
DOI: 10.1097/jsm.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Novel Factors Associated With Analgesic and Anti-inflammatory Medication Use in Distance Runners: Pre-race Screening Among 76 654 Race Entrants—SAFER Study VI

Abstract: 12.2% runners use AAIM before and/or during races, mostly NSAIDs. Factors (independent of sex, age, and race distance) associated with AAIM use were history of injuries, EAMC, and numerous chronic diseases. We suggest a pre-race screening and educational program to reduce AAIM use in endurance athletes to promote safer races.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
(115 reference statements)
0
14
1
Order By: Relevance
“…Despite accumulating evidence on the potential harmful effects of NSAIDs and the absence of studies that convincingly prove significant exercise performance benefits from taking NSAIDs [ 39 , 40 ], many runners still use them, with various motivations. Older age, female gender, competing on a longer distance, history of injuries and exercise-associated muscle pains were associated with a higher probability to take NSAIDs before/during competition by long-distance runners [ 12 ]. With or without the use of NSAID, there is no evidence that practicing a sport can lead to the development of chronic kidney disease [ 35 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite accumulating evidence on the potential harmful effects of NSAIDs and the absence of studies that convincingly prove significant exercise performance benefits from taking NSAIDs [ 39 , 40 ], many runners still use them, with various motivations. Older age, female gender, competing on a longer distance, history of injuries and exercise-associated muscle pains were associated with a higher probability to take NSAIDs before/during competition by long-distance runners [ 12 ]. With or without the use of NSAID, there is no evidence that practicing a sport can lead to the development of chronic kidney disease [ 35 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the findings of previous studies, we demonstrated that ibuprofen or diclofenac were most frequently used by runners. 18,21,23 At the same time, a surprisingly high number of participants in the current study tested positive for paracetamol. Low self-reporting levels of NSAIDs/analgesics used in relation to the running event in our study may be explained by a low perception of risks related to the occasional intake of these medications.…”
Section: Discussionmentioning
confidence: 51%
“…6,18,24 Interestingly, a recent study involving 76,654 race entrants of the 21.1-and 56-km runs showed that only 12.2% (CI 95%, 12.0-12.5) of the respondents reported the use of NSAIDs/analgesics before/during the running event. 21 Thus, the estimated prevalence of the NSAIDs/analgesics used in relationship with endurance running varies significantly among different studies and requires further investigation. This study showed that urine samples of 32.5% half-marathoners and 15.6% of the 10-km contestants were positive for the presence of NSAIDs/analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The online medical screening tool consisted of a series of questions that were developed to specifically provide clinical information for medical staff in order to improve medical care on race day. The main sections of the medical screening tool were based on the guidelines for cardiovascular evaluation of middle-aged/senior individuals engaging in leisure-time sport activities (Position stand from the European Association of Cardiovascular Prevention and Rehabilitation) (Borjesson et al, 2011), and adapted from our previous studies in distance runners (Rotunno et al, 2018;Schwabe et al, 2018). The detailed methodology of the online medical screening tool development and implementation was described in previous studies amongst endurance runners (Rotunno et al, 2018;Schwabe et al, 2018).…”
Section: Methodsmentioning
confidence: 99%